The utilization of efgartigimod in the treatment of acute cerebellar ataxia: a case report - Yang, Liu L.; Ruan, Yushuang; Cai, Fucheng; Xia, Yuanpeng (Frontiers in Immunology, 2025)
BackgroundAcute cerebellar ataxia (ACA) is the most common cause of acute ataxia in children and adolescents. It is a cerebellar disorder with multifactorial pathogenesis, often triggered by viral or bacterial infections, as well as autoimmune mechanisms. The clinical course of ACA can vary widely, ranging from a benign, self-limiting condition to a severe, life-threatening illness. There is no universally accepted consensus on the optimal management of ACA in children. While steroids and immunoglobulins are commonly used, some patients may not respond adequately to these treatments. Efgartigimod, a novel immune modulator, has not been previously reported in the treatment of ACA, but its unique mechanism of action suggests potential therapeutic benefits.Case presentationWe present a case of an 11-year-old girl with ACA who was treated with efgartigimod and showed significant improvements. The patient presented with acute ataxia, slurred speech, vomiting, diarrhea, abdominal pain, dizziness, and altered mental status. Initial investigations, including routine blood tests, specific autoantibodies related to cerebellitis in both serum and cerebrospinal fluid (CSF), and brain magnetic resonance imaging (MRI) revealed no abnormalities. Despite treatment with neurotrophic drugs and dexamethasone, the patient showed minimal improvement. A trial of efgartigimod (10 mg/kg) resulted in rapid symptom alleviation within three days.ConclusionThis case highlights the potential role of efgartigimod in the treatment of ACA, particularly in cases refractory to conventional therapies. Further studies are needed to validate the efficacy and safety of Efgartigimod in pediatric patients with ACA.